1988
DOI: 10.1139/f88-192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Exposure to Acid, Aluminum, and Low Calcium on Adult Brook Trout (Salvelinus fontinalis). 1. Survival, Growth, Fecundity, and Progeny Survival

Abstract: Adult brook trout (Salvelinus fontinalis) were exposed to concentrations of acid, Al, and Ca representative of acidic and acid-sensitive surface waters. At low pH (4.42–5.03), survival and growth were reduced by elevated Al concentrations (486 μg/L) and low Ca concentrations (0.5 mg/L). Fecundity (number of eggs per female) was reduced by exposure to some treatment combinations, but this effect was mediated through reduced growth; number of eggs per unit body weight was not related to treatment. Viability of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

1990
1990
1997
1997

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 18 publications
2
32
1
1
Order By: Relevance
“…6-0.7 of the values at pH near 6.5 (Ingersoll et al 1990, Marschall 1991. For adult fish, this change in pH did not affect survival, though it caused growth rates to be 0.5-0.8 of the pH 6.5 growth rates (Mount et al 1988, Marschall 1991. Although these vital rate responses are above the ~0 .…”
Section: Local Extinctionsmentioning
confidence: 96%
See 1 more Smart Citation
“…6-0.7 of the values at pH near 6.5 (Ingersoll et al 1990, Marschall 1991. For adult fish, this change in pH did not affect survival, though it caused growth rates to be 0.5-0.8 of the pH 6.5 growth rates (Mount et al 1988, Marschall 1991. Although these vital rate responses are above the ~0 .…”
Section: Local Extinctionsmentioning
confidence: 96%
“…In systems stressed by acidic deposition, growth rates of juveniles and adults are positively correlated with pH and calcium concentration. Again, the effect is strongest on juveniles (Mount et al 1988, Ingersoll et al 1990, Marschall 1991. Neither fecundity (per body mass) nor egg size is affected by pH and calcium concentration (Mount et al 1988).…”
Section: Habitat Alterationmentioning
confidence: 96%
“…Physiological studies have demonstrated that Al causes acute ionoregulatory and respiratory disturbances in this pH range (e.g., Neville 1985;Playle et al 1989;Witters et al 1990). However, the continued presence of fish populations in softwater lakes and rivers containing levels of aluminium in excess of 100 lzg/l at these pH's (Wright and Snekvik 1978;Schofield and Trojnar 1980;Kelso et al 1986) has encouraged research into the effects of chronic exposure to sublethal Al concentrations in acidified low Ca 2 + water (Wood and McDonald 1987;Mount et al 1988;McDonald and Milligan 1988;Wood et al 1988a,b;Walker et al 1991). …”
Section: Introductionmentioning
confidence: 99%
“…Salmonids living in low pH waters grow more slowly than those in neutral or alkaline waters (Edwards & Hjeldens 1977, Rosseland et al 1980, Lacroix et al 1985, Mount et al 1988). The Atlantic salmon exposed to low pH in this study were shorter and lighter than their control counterparts.…”
Section: Discussionmentioning
confidence: 99%